Popeye [videorecording (DVD)] - Williams, Robin, 1951-2014; Duvall, Shelley, 1949-; Walston, Ray, 1917-2001 (Paramount Home Entertainment, 2017)
Live-action version of the popular cartoon with Olive Oyl and Sweet Pea.